Explaining juvenile idiopathic arthritis to paediatric patients using illustrations and easy-to-read texts: improvement of disease knowledge and adherence to treatment - Christiane Reiser (BMC, 2021)
Abstract Introduction Juvenile idiopathic arthritis (JIA) is the leading chronic rheumatic disease in childhood. To achieve adherence to therapy, in-depth understanding of disease and treatment options are important. Objective Development of specifically designed illustrations and standardised, easy-to-read texts for children and adolescents with JIA. Education materials were tested for comprehensibility and content validity. We hypothesised that children would be able to increase their knowledge about JIA after presentation of materials. Methods The illustrations were designed by a graphic artist and the informative texts consecutively transformed to easy-to-read language. The materials appear as a modular system to allow individualized information for each patient. The illustrations and texts were tested for knowledge gain and improvement of self-efficacy in children affected by JIA/ rheumatic diseases and controls. Health-related quality of life (HRQoL) was tested as an overall assessment of patients’ well-being. Results 46 controls (71% female) and 38 patients (48% female) with a median age of 11 years were tested in a standardised setting. In both groups knowledge gain was significant (controls: t (44) = 11.08, p < 0.001, d = 1.65; patients: t (37) = 7.48, p < 0.001, d = 1.21). The control group had a significantly higher enhancement of disease knowledge compared to patients’ group (p = .046) The follow-up testing was only performed in one school class (20 controls) due to Covid-19 pandemic with significant improvement compared to the pre-test results (p = .002). The enhancement of self-efficacy through the teaching session was significantly higher in the patients’ group. No impairment of HRQoL was seen. Conclusion Explaining juvenile rheumatic diseases and therapeutic strategies is an important task in paediatric rheumatology. To avoid incomprehensible explanations in medical jargon, illustrations and easy-to-read texts were developed. Standardised presentation of the newly created materials resulted in a significant improvement of disease knowledge in patients and controls in addition to an enhancement of self-efficacy in patients.